Influence of nanoparticles on color stability, microhardness, and flexural strength of acrylic resins specific for ocular prosthesis - Andreotti AM (Dove Medical Press, 2014)
Agda Marobo Andreotti, Marcelo Coelho Goiato, Amália Moreno, Adhara Smith Nobrega, Aldiéris Alves Pesqueira, Daniela Micheline dos Santos Araçatuba Dental School, São Paulo State University, Araçatuba, São Paulo, Brazil Abstract: The aim of this study was to assess the effect of adding nanoparticles to N1 acrylic resin intended for artificial sclera, in terms of the color stability, microhardness, and flexural strength of the resin. Three hundred samples of N1 acrylic resin were used: 100 samples for color stability and microhardness tests (each test was performed on the opposite side of each sample), and 200 samples for flexural strength testing (100 samples before and after 1,008 hours of accelerated aging). Samples for each test were separated into ten groups (n=10), ie, without nanoparticles (control group) or with nanoparticles of zinc oxide, titanium dioxide (TiO2), and barium sulfate at weight concentrations of 1%, 2%, and 2.5% (nanoparticle groups). Data were subjected to statistical analysis with nested analysis of variance and Tukey’s test (P<0.05 significance level). Among the nanoparticle groups, the TiO2 groups showed better color stability at all concentrations. Microhardness values increased after artificial aging, except for the control and zinc oxide groups. After aging, the 1%–2% TiO2 groups had significantly higher microhardness values compared with the other nanoparticle groups. Before aging, there was a significant difference in flexural strength between the control and nanoparticle groups. After aging, the control and TiO2 groups, regardless of concentration, showed the lowest flexural strength values. Incorporation of nanoparticles directly influenced the acrylic resin properties, with TiO2 being the most influential nanoparticle in terms of the evaluated properties. Keywords: acrylic resins, eye, artificial, color, hardness, nanoparticles